Environmental Impact of Food with an Interactive Data Visualization Exhibit: A study of Universeum’s visitors’ perceptions and experienced learning when using visualization exhibits about sustainable food consumption - Liderfors, Malou; Lövgren, Sandra (My University, 2022)
The climate is changing, and many commitments must be made to slow down that change. However, many people seem to not know how big the environmental impacts of food are, and what environmentally-friendly food is. At the same time, the visu- alization of data is becoming a popular tool for educating people. The science center Universeum in Gothenburg has opened a new public visualization exhibition called Vislab, focusing on sustainable development and what impact different choices have on our planet. This study is based on a climate-smart visualization exhibit about food consumption at Vislab, and aims to investigate the role a visualization exhibit can play in educating the public about different foods’ environmental impact. Many participants believed locally produced food to be environmentally friendly, and seemed to know how to reduce their environmental impact from food con- sumption but choose not to. 47.1 % of the participants appeared to have problems interpreting the data visualizations, with no significant differences between genders, ages, or educational backgrounds. The males were significantly better at choos- ing environmentally friendly food than the females were, but no similar differences were found between participants of different ages or educational backgrounds. Most participants seemed to learn about specific food items’ environmental impact and 19.6 % commented on how they should change their diet, indicating deeper learn- ing. These findings support the idea of visualization being suitable for educating people regardless of their background about climate change, but it is important to continuously identify and correct eventual deceptive features which can jeopardize the exhibit’s purpose.
Keywords: interactive data visualisation; learning; science centre; food consumption